V2 Trigeminal Referred Pain from Chronic Occipital Neuralgia Caused by Entrapment of the Greater Occipital Nerve - Lee, Chang-ik; Son, Byung-chul (Indian Journal of Neurosurgery, 2019)
Although entrapment of the greater occipital nerve (GON) is a well-known cause of occipital neuralgia, occurrence of referred hemifacial trigeminal pain involving V2 distribution from chronic occipital neuralgia is rare. A 67-year-old female patient with intermittent left-sided occipital neuralgia of 10-year duration presented with a new onset of left-sided hemifacial pain of 5-month duration. With aggravation of left-sided occipital neuralgia, continuous burning pain and paresthesia gradually developed in her left malar and periorbital area. They also spread to her left upper lip. Severe compression of the left GON by tendinous aponeurotic attachment of the trapezius was found intraoperatively. Decompression of the left GON from chronic entrapment resulted in immediate relief for her hemifacial pain and chronic occipital neuralgia. These findings provide clinical affirmation of the existence of trigeminal/cervical convergence and hypersensitivity. Chronic irritating afferent input of occipital neuralgia caused by entrapment of the GON seems to be associated with sensitization and hypersensitivity of the second-order neurons in the trigeminocervical complex receiving convergent input from dural and cervical structures. Referred trigeminal pain from chronic occipital neuralgia may extend to V2 in addition to V1 trigeminal distribution.
Keywords: decompression; greater occipital nerve; lacrimation; occipital neuralgia; trigeminocervical complex